Airborne measurements and emission estimates of greenhouse gases and other trace constituents from the 2013 California Yosemite Rim wildfire. (February 2016) - Yates, E.L.; Iraci, L.T.; Singh, H.B.; Tanaka, T.; Roby, M.C.; Hamill, P.; Clements, C.B.; Lareau, N.; Contezac, J.; Blake, D.R.; Simpson, I.J.; Wisthaler, A.; et al.
Abstract: This paper presents airborne measurements of multiple atmospheric trace constituents including greenhouse gases (such as CO2, CH4, O3 ) and biomass burning tracers (such as CO, CH3 CN) downwind of an exceptionally large wildfire. In summer 2013, the Rim wildfire, ignited just west of the Yosemite National Park, California, and burned over 250, 000 acres of the forest during the 2-month period (17 August to 24 October) before it was extinguished. The Rim wildfire plume was intercepted by flights carried out by the NASA Ames Alpha Jet Atmospheric eXperiment (AJAX) on 29 August and the NASA DC-8, as part of SEAC 4 RS (Studies of Emissions, Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys), on 26 and 27 August during its intense, primary burning period. AJAX revisited the wildfire on 10 September when the conditions were increasingly smoldering, with slower growth. The more extensive payload of the DC-8 helped to bridge key measurements that were not available as part of AJAX (e. g. CO). Data analyses are presented in terms of emission ratios (ER), emission factors (EF) and combustion efficiency and are compared with previous wildfire studies. ERs were 8.0 ppb CH4 (ppm CO2 ) −1 on 26 August, 6.5 ppb CH4 (ppm CO2 ) −1 on 29 August and 18.3 ppb CH4 (ppm CO2 ) −1 on 10 September 2013. The increase in CH4 ER from 6.5 to 8.0 ppb CH4 (ppm CO2 ) −1 during the primary burning period to 18.3 ppb CH4 (ppm CO2 ) −1 during the fire's slower growth period likely indicates enhanced CH4 emissions from increased smoldering combustion relative to flaming combustion. Given the magnitude of the Rim wildfire, the impacts it had on regional air quality and the limited sampling of wildfire emissions in the western United States to date, this study provides a valuable dataset to support forestry and regional air quality management, including observations of ERs of a wide number of species from the Rim wildfire. Highlights: Airborne measurements of trace gases downwind of an exceptionally large wildfire. Measurements during the Rim wildfire intense and smoldering burning phases. Assessment of emission ratios, emission factors and combustion efficiency. Dataset to support forestry and regional air quality management.